Measuring the impact of foreign direct investment on exports in a sample of middle-income developing countries for the period (1990-2020) - Alaa Shaker Mahmood Al-Douri; Saad Mahmood Khaleel Al-Kawaz (Tikrit Journal of Administrative and Economic Sciences, 2024)
Foreign direct investment is considered one of the most important sources of capital flows. It is also considered one of the basic pillars that enable the investment of the country’s human and natural resources. Foreign investment can play an important role in this process, as it is intended to use the investor’s surplus funds in investment tools and opportunities available in the markets. Foreign investments outside the borders of the resident investor’s country. These investments differ from local investments in terms of the nature of the investment instruments used, the currencies traded, and the degree of risks to which the investor is exposed.